MODERNISASI, LAYAR MONITOR, DAN PERUBAHAN BUDAYA - Khadijah Aufadina; Mochamad Irfansyah (Universitas Hasanuddin, 2021)
Modernization that occurs in society today has led to the emergence of industrial acceleration and new technology. One of the most influential elements of modernization is the technology on the monitor screen. The purpose of this study is to determine the cultural changes that have occurred in Sumbermulyo Village, Jombang. The theory used in this research is cultural materialism initiated by Marvin Haris. The results showed that the culture that occurred in the Sumbermulyo Village community was greatly influenced by changing ethical behavior in the community. The culture that is still sustainable today is Mahabaturrasul. However, the organizers are still dominated by older people who have been active in this event since they were young. The cause of cultural change in Sumbermulyo Village is the effect of sedentary behavior which includes a large number of activities in the house due to frequent viewing of the monitor screen.